How to identify when a performance indicator has run its course. (6th April 2010) - Reeves, David; Doran, Tim; Valderas, Jose M; Kontopantelis, Evangelos; Trueman, Paul; Sutton, Matt; Campbell, Stephen; Lester, Helen
Abstract : In April 2011 eight clinical indicators will be removed from the UK Quality and Outcomes Framework. David Reeves and colleagues explain why they were chosen and suggest a rationale for future decisions